Factores de riesgo para desarrollar hernia incisional en pacientes atendidos de cirugía abdominal - Llamoga Cuenca, Luis Joseph (2020)
When reviewing the national medical literature, no recent publications were found that analyze the risk factors related to the appearance of incisional hernias of the abdominal wall. Nor have any research been published in the La Libertad Region that seeks to find those risk factors directly linked to the recurrence of incisional hernias in local patients. Therefore, with this research project, it was proposed to try to identify those factors associated, both depending on the patient and the surgical technique used by the surgeon, with the first recurrence of an incisional hernia of the abdominal wall. The direct or indirect impact on these factors could alter the natural course that this disease has been presenting in the country so far. Concluding that obesity, jaundice and operative wound infection; constitute risk factors for Incisional Hernia.